PENGARUH PILIHAN METODE NILAI WAJAR PROPERTI INVESTASI TERHADAP NILAI PERUSAHAAN REAL ESTATE - Stefanus Angelo; Nunung Nuryani (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2021)
IAS 40 (adopted in PSAK 13, 2012) about investment properties allowing companies to choose the method of measuring their investment properties, namely the cost method and the fair value method. Side that oppose fair value method argue that fair value is unreliable and costly. The purpose of this study, therefore, is to examine the relevance of the fair value accounting choice method and determinants that affect of fair value accounting choice method for investment property. This research is using secondary data observation technique which acquired from annual financial reports for real estate, manufacturing, and trading sector companies listed on the Indonesia Stock Exchange during the 2012-2016 period. By using judgment sampling method, the research sample tested were 48 companies (19 real estate companies, 15 manufacturing companies, and 14 trading companies). The results of this research shows that fair value accounting choice method has a positive significant on firm value. In that case shows that fair value accounting choice have a value relevance so it can help investor to make a investment decision. For determinants of fair value accounting choice, that firm size variables has significant positive and leverage significant negatively with determinants of fair value accounting choice while big four has no effect on determinants of fair value accounting choice. Keywords: Value relevance, Investment property, Firm size, Leverage, Big four. References: Acaranupong, K. (2017). Accounting practices and value relevance of investment property: Evidence from firms listed on the stock exchange of Thailand. Asian Journal of Business and Accounting, 10(2), 1–41. Ahmad, F. B., & Mohammad, A. (2015). The Effect of Fair Value Accounting on Jordanian Investment Properties. International Journal of Financial Research, 6(4), 99–113. Al-Khadash, H. A., & Ahmad, K. (2014). The Effects of the Fair Value Option under IAS 40 on the Volatility of Earnings. Journal of Applied Finance & Banking, 4(5), 95–113. Al-khadash, H., & Abdullatif, M. (2009). Consequences of fair value accounting for financial instruments in the developing countries: the case of banking sector in Jordan. Jordan Journal of Business Administration, 5(4). Alhusaini, W., & Mostafa, E. (2016). Accounting for property investment : an examination of the value relevance of unrealised gains and losses recognised under IAS 40 Walid Alhusaini and Mostafa Elshamy *, 6(2), 100–117. Barth, M. E. (2000). Valuation-based accounting research: Implications for financial reporting and opportunities for future research. Accounting and Finance, 40(1), 7–31. Beisland, L. A. (2009). A Review of the Value Relevance Literature. The Open Business Journal, 2(1), 7–27. Carroll, T., Linsmeier, T., & Petroni, K. (2003). The Reliability of Fair Value versusHistorical Cost Information: Evidence from Closed-End Mutual Funds. Journal of Accounting, Auditing & Finance, 18(1), 1. Chen, K. L., Road, S. S., & Tsang, D. (2013). Earnings management , firm location , and financial reporting choice: An analysis of fair value reporting for investment properties in an emerging market. Christensen, H. B., & Nikolaev, V. V. (2009). Who uses fair value accounting for non-financial assets after IFRS adoption. SSRN Working Paper, (9), 1–46. DeAngelo, L. E. (1981). AUDITOR SIZE AND AUDIT QUALITY. Journal of Accounting and Economics, 3(May), 183–199. Farahmita, A., & Siregar, S. V. (2014). FAKTOR-FAKTOR YANG MEMPENGARUHI KEMUNGKINAN PERUSAHAAN MEMILIH METODE NILAI WAJAR UNTUK PROPERTI INVESTASI. Simposium Nasional Akuntansi XVII, 1–21. FASB. (1980). Statement of Financial Accounting Concepts No. 2 - Qualitative Characteristics of Accounting Information. FASB Concepts Statements, (2), 0. Ferri, M. G., & Jones, W. H. (1979). Determinants of financial structure: A new methodological approach. American Finance Association, 34(3), 631–644. Hendriksen, E. S., & Breda, M. F. Van. (2001). Accounting Theory. Irwin Profesional Publishing. Jabar, A., & Mohamed, A. (2015). The practices of fair value reporting on investment property in Malaysia, (August). Muller, K. A., Riedl, E. J., & Sellhorn, T. (2008). Causes and Consequences of Choosing Historical Cost versus Fair Value, 1–49. Muller, K., Riedl, E. J., & Sellhorn, T. (2008). Consequences of Voluntary and Mandatory Fair Value Accounting: Evidence Surrounding IFRS Adoption in the EU Real Estate Industry, (June 2014), Working Paper 1-43. Quagli, A., & Avallone, F. (2010). Fair value or cost model? Drivers of choice for IAS 40 in the real estate industry. European Accounting Review, 19(3), 461–493. Souza, F. Ê. A. de, Botinha, R. A., Silva, P. R., & Lemes, S. (2015). Comparability of Accounting Choices in Future Valuation of Investment Properties: An Analysis of Brazilian and Portuguese Listed Companies. Revista Contabilidade & Finanças, 26(68), 154–166. Subramanyam, K. R. (2014). Financial Statement Analysis (11th ed.). McGraw-Hill. Tan, M. Z., Mohamat Sabri Hassan, & Embong, Z. (2014). Value Relevance of Investment Properties’ Fair Value and Board Characteristics in Malaysian Real Estate Investment Trusts. Asian Journal of Accounting and Governance, 5, 1–13. Weygandt, J. J., Kimmel, P. D., & Kieso, D. E. (2013). Financial Accounting (IFRS). John Wiley & Sons, Inc. Wooten, T. C. (2003). Research About Audit Quality. The CPA Journal.